Rising trend of youth-onset diabetes: A new challenge to the nation: Rising trend of youth-onset diabetes (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Abstract not availableJ Assoc Clin Endocrinol Diabetol Bangladesh, January 2024; 3(1): 1-2